Cortical DC potential shifts accompanying the central processing of visually presented analogue and digital time displays - Ebenbichler, G; Uhl, F; Lang, W; Lindinger, G; Egkher, A; Deecke, L (Neuropsychologia, 1997)
According to studies in brain-lesioned patients, the cortical substrate subserving the reading of digitally presented time displays seems to differ from that of reading analogue displays. While the right hemisphere has been assumed to be important for reading analogue displays, reading digital displays is attributed to the left hemisphere. This study attempts to localize the cortical substrate of reading analogue versus digital time displays in the intact human brain using scalp-recorded event-related slow negative DC potential shifts. In the arithmetic tasks, subjects had to judge whether or not the time conveyed by the last out of three tachistoscopically presented (analogue or digital) slides was the exact difference between the time conveyed by the first and the second slide. In the control condition, subjects only had to attend to (analogue or digital) time displays. With analogue slides, frontolateral recording sites revealed a right hemispheric preponderance of DC shifts measured in the interval between the second and third slide. Anterior temporal recording sites revealed a right hemispheric preponderance only when calculations were performed. By contrast, there was no hemispheric lateralization with digital slides. The arithmetic versus control manipulation modulated waveforms, but did not influence hemispheric laterality.